Physiotherapy management of joint hypermobility syndrome – a focus group study of patient and health professional perspectives. Issue 1 (March 2016) - Palmer, S.; Terry, R.; Rimes, K.A.; Clark, C.; Simmonds, J.; Horwood, J.
Abstract: Objective: To develop an understanding of patient and health professional views and experiences of physiotherapy to manage joint hypermobility syndrome (JHS). Design: An explorative qualitative design. Seven focus groups were convened, audio recorded, fully transcribed and analysed using a constant comparative method to inductively derive a thematic account of the data. Setting: Four geographical areas of the UK. Participants: 25 people with JHS and 16 health professionals (14 physiotherapists and two podiatrists). Results: Both patients and health professionals recognised the chronic heterogeneous nature of JHS and reported a lack of awareness of the condition amongst health professionals, patients and wider society. Diagnosis and subsequent referral to physiotherapy services for JHS was often difficult and convoluted. Referral was often for acute single joint injury, failing to recognise the long-term multi-joint nature of the condition. Health professionals and patients felt that if left undiagnosed, JHS was more difficult to treat because of its chronic nature. When JHS was treated by health professionals with knowledge of the condition patients reported satisfactory outcomes. There was considerable agreement between health professionals and patients regarding an 'ideal' physiotherapy service. Education was reported as an overarching requirement for patients and health care professionals. Conclusions: Physiotherapy should be applied holistically to manage JHS as a long-term condition and should address injury prevention and symptom amelioration rather than cure. Education for health professionals and patients is needed to optimise physiotherapy provision. Further research is required to explore the specific therapeutic actions of physiotherapy for managing JHS.